Tunable Multiphase Oscillator Using Diamond Transistors with Voltage Controlled Condition of Oscillation for Amplitude Stabilization - Jerabek, J.; Sotner, R.; Vrba, K. (Elektronika ir Elektrotechnika, 2014)
The main aim of this paper is to present simple and low-cost solution of oscillator utilizing very simple method for automatic amplitude stabilization using adjustable current gain control. It provides satisfying total harmonic distortion results and adjusting of oscillation frequency over one decade. Experimental results confirmed workability and gave opportunity to consider and evaluate practically achievable performances of this oscillator type. DOI: http://dx.doi.org/10.5755/j01.eee.20.1.6166